Macro news and stock returns in the euro area: A VAR-GARCH-in-mean analysis - Guglielmo Maria Caporale; Fabio Spagnolo; Nicola Spagnolo (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper analyses the effects of newspaper coverage of macro news on stock returns in eight countries belonging to the euro area (Belgium, France, Germany, Greece, Ireland, Italy, Portugal and Spain) using daily data for the period 1994-2013. The econometric analysis is based on the estimation of a VAR-GARCH-in-mean model. The results can be summarised as follows. Positive (negative) news have significant positive (negative) effects on stock returns in all cases. Their volatility has a significant impact on both stock returns and volatility; specifically, an increase in news volatility is always associated with a decrease in stock returns. Markets are particularly responsive to negative news, and the reaction is bigger in the PIIGS countries, and during the recent crisis period.
Keywords: C32; F36; G15; 330; Macro news; Volatility spillovers; VAR-GARCH-in-mean model